Multiraciality and mental health: the Cultural Formulation Interview as an instrument for exploring in-between identities and third spaces - Strand, Mattias; Osanami Törngren, Sayaka (Frontiers in Psychiatry, 2025)
The multiracial population has grown substantially across the Global North, with Sweden having one of the largest per capita mixed populations worldwide. Despite this demographic shift, mental healthcare practitioners are often unprepared to address the complex experiences of mixed individuals, who navigate ambiguous racial and ethnic spaces that challenge traditional monolithic categories. We here include transracial adoptees as part of the mixed population, recognizing their unique experiences of racialized in-betweenness. Historical narratives have long pathologized mixed individuals through harmful stereotypes such as the “tragic mulatto” and “marginal man”, portraying them as inherently maladjusted. Contemporary research presents mixed findings regarding mental health outcomes in multiracial populations, with some studies reporting higher rates of anxiety, depression, and suicidal ideation, while others find no substantial differences compared to monoracial groups. This article argues for a more nuanced, person-centered approach to understanding mixed identity in healthcare and foregrounds the Cultural Formulation Interview (CFI) as a valuable clinical instrument. The ethnographic framework of the CFI enables exploration of complex identity negotiations, experiences of racism and discrimination, and available resources without reinforcing deficit perspectives. By fostering culturally attuned practices, mental healthcare can better serve an increasingly diverse society and address the multilayered experiences of multiracial individuals.